ARTECH 2021 - Book of Proceedings of the 10th International Conference on Digital and Interactive Arts - Hybrid Praxis – Art, Sustainability & Technology - Lopes, Maria Manuela (2022)
Book of proceedings of the 10th edition of ARTECH - the International Conference on Digital and Interactive Arts, Centro de Congressos de Aveiro, Aveiro, Portugal 13-15 October 2021.